Sequencing and analysis of the complete mitochondrial genome of the large mole (Mogera robusta) from China - Liu Zhu; Wang Ao-nan; Li Jiao-Jiao (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitogenome sequence of the large mole (Mogera robusta) was determined using long PCR. The genome was 16,890 bp in length and contained 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, one origin of L strand replication, and one control region. The overall base composition of the heavy strand is A (35.2%), C (22.8%), T (29.1%), and G (12.9%). The base compositions present clearly the A–T skew, which is most obviously in the control region and protein-coding genes. Mitochondrial genome analyses based on MP, ML, NJ, and Bayesian analyses yielded identical phylogenetic trees. The two Mogera species formed a monophyletic group with the high bootstrap value (100%) in all examinations.